Lease Capitalization and the Transaction Concept. - Rappaport, Alfred (The Accounting Review, 1965)
This article discusses the controversy over accounting for leases. The current controversy over accounting for leases highlights once again the necessity for accelerated research in basic accounting theory. Some opponents of lease capitalization have argued that lease contracts involve executory, equally unperformed services; hence, they are not recordable according to the prevailing conception of an accounting transaction. There is, however, no persuasive rationale for the exclusion of this class of commitments. Indeed, the decision to exclude the financial effects of such commitments from the accounts is contrary to accepted concepts of assets and liabilities widely held by accountants today. As with any other reporting problem, the ultimate decision to accept or reject a proposed solution should be based on its expected contribution toward making accounting statements more meaningful. If lease capitalization is judged to be consistent with sound accounting theory, then its rejection can be validly based only on the magnitude of the probable error in its calculation.